Optimum Remedial Operation of Permanent Magnet Synchronous Motor - Hamdy Mohamed Soliman; S. M. EL. Hakim (Institute of Advanced Engineering and Science, 2012)
In critical systems, the reliability of the drive is very important. The faults are unwanted. The faults may be lead to loss of the human life and capital. This paper is addressed this problem and suggested two models to solve it. The first model doesn’t contain any special tools to improve the torque ripple and THD. The second model contains 2PI current controllers to improvement the performance at fault and remedial operation. One is for the torque and the other is for the flux. The first PI controller is feeding from the torque error between the reference and estimated torques to get new q-axis current component representing modifier current arises from uncertain things inside the machine and drive system such as temperature and parameters variations. This current will add to reference q-axis current to get robust new q-axis current to satisfy the drive requirement and solve the torque problem (ripple torque). With robust current, the total harmonic distortion is a decrease but doesn’t reach the best value so the other PI controller is used to adjust the THD. In this PI controller, the d-axis flux is compared to rotor permanent magnet flux to solve this problem arises from non-sinusoidal of the magnetic flux. The output of the PI controller is introduced to the reference d-axis current. The new d-axis current will reach the best value of THD. The simulation of the second controller is compared to the simulation of first controller to show if the second controller strong or weak. Matlab simulink is used to simulate the drive system.DOI:http://dx.doi.org/10.11591/ijece.v2i5.725